Fizicheskaya nagruzka i allergiya - Galiyev, R. S.; Golytsina, I. I.; Zamogilnov, A. I. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of the study was to analyse the influence of the moderate physical loadings on the development and course of a desease of the immediate type allergy. The results had shown that the moderate physical loadings performs the hyposensibilizing influence on an organism. They can be recomended for the treatment (at the stage of remission) and prophylaxis of the allergic illnesses. The medicinal and prophylactic effect of the dayly moderate physical loading is more expressed in adults, than in children.